2018
DOI: 10.18553/jmcp.2018.17507
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Health Care Resource Utilization, and Costs Associated with Nonadherence to Antiretrovirals in Medicaid-Insured Patients with HIV

Abstract: This study was supported by Janssen Scientific Affairs, which was involved in the study design, data collection, data analysis, manuscript preparation, and publication decisions. Emond, Lafeuille, Romdhani, and Lefebvre are employees of Analysis Group, a consulting company that received research grants from Janssen Scientific Affairs to conduct this study. Dunn, Woodruff, Pesa, and Tandon are current employees and stockholders of Johnson & Johnson, owner of Janssen Scientific Affairs. Jiao was an employee of J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
7
0
4
Order By: Relevance
“…These observations suggest that Medicaid-insured patients are treated with medications and formulations that are not adapted to a high level of nonadherence, which was previously reported to be as high as 60%-80% in this population. 32,44 Third, as previously reported in another study, the commercially insured population predominantly consisted of male patients, whereas the Medicaidinsured population proportionally comprised more female patients. 32 In 2017, the U.S. Census Bureau reported that the median household income of same-sex male couples was 17.4% higher than that of married opposite-sex couples and 58.8% higher than that of unmarried opposite-sex couples.…”
Section: Rapid Initiation Of Antiretroviral Therapy Following Diagnosis Of Human Immunodeficiency Virus Among Patients With Commercial Inmentioning
confidence: 52%
“…These observations suggest that Medicaid-insured patients are treated with medications and formulations that are not adapted to a high level of nonadherence, which was previously reported to be as high as 60%-80% in this population. 32,44 Third, as previously reported in another study, the commercially insured population predominantly consisted of male patients, whereas the Medicaidinsured population proportionally comprised more female patients. 32 In 2017, the U.S. Census Bureau reported that the median household income of same-sex male couples was 17.4% higher than that of married opposite-sex couples and 58.8% higher than that of unmarried opposite-sex couples.…”
Section: Rapid Initiation Of Antiretroviral Therapy Following Diagnosis Of Human Immunodeficiency Virus Among Patients With Commercial Inmentioning
confidence: 52%
“…In period 1, around 40% of PLHIV were aged between 18 and 39 years, while in periods 2 and 3 the percentage doubled (around 75% and 80%, respectively). This change in the profile of new PLHIV is attracting attention in HIV/AIDS treatment adherence studies, especially in adolescents and young people in peripheral areas, due to the risks that these age groups are exposed to, such as social vulnerability, injectable drug sharing, and unprotected sex, among others (Dunn et al, 2018;Taquette and Rodrigues, 2019). In addition, this population exhibited a concerning Frontiers in Pharmacology frontiersin.org higher viral load at the end of the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these data, adherence was classified, according to the literature, as optimal (dispensation record greater than or equal to 95% of the period analyzed), good (between 80 and less than 95%) and low (less than 80%) (Castillo-Mancilla and Haberer, 2018;Dunn et al, 2018). For purposes of the statistical analysis of relative risk, adherence was classified as optimal/good (dispensation record greater than or equal to 80% of the period analyzed) and low (less than 80%).…”
Section: Information Sources and Data Analysismentioning
confidence: 99%
“…With effective antiretroviral (ART) therapy, HIV infection becomes a manageable chronic condition [ 3 , 4 ]. As a result, the number of people living with HIV (PLWH) is increasing, and life expectancy is longer than before [ 4 ].…”
Section: Introductionmentioning
confidence: 99%